2005
DOI: 10.1016/j.cardiores.2005.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-1 plays a major role in vascular inflammation and atherosclerosis in male apolipoprotein E-knockout mice

Abstract: Our results demonstrate that the IL-1/IL-1Ra ratio plays a critical role in the pathogenic mechanisms leading to vascular inflammation and atherosclerosis in ApoE -/- mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
124
0
7

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(135 citation statements)
references
References 33 publications
4
124
0
7
Order By: Relevance
“…MOS did not affect specific markers of systemic inflammation associated with atherosclerosis,31 despite having anti‐inflammatory properties in previous studies 11, 12, 13. However, we cannot exclude the possibility that MOS might have modulated other systemic immune markers or that it has affected the immune status more subtly or locally, for example within the atherosclerotic plaque.…”
Section: Discussionmentioning
confidence: 63%
“…MOS did not affect specific markers of systemic inflammation associated with atherosclerosis,31 despite having anti‐inflammatory properties in previous studies 11, 12, 13. However, we cannot exclude the possibility that MOS might have modulated other systemic immune markers or that it has affected the immune status more subtly or locally, for example within the atherosclerotic plaque.…”
Section: Discussionmentioning
confidence: 63%
“…IL-1RI deficiency diminished aortic lesions, whereas IL-1RA deficiency exacerbated them, in ApoE-deficient mice fed high fat/high cholesterol "Western" diets, suggesting that IL-1RA tonically opposes a contributing role of endogenous IL-1 (acting via IL-1RI) in such lesion formation (18). IL-1RI deficiency also reduced aortic lesions in mice infected systemically with Porphyromonas gingivalis, a periodontal pathogen, indicating a mediating role of IL-1RI in microbially induced vasculopathy (8).…”
Section: Discussionmentioning
confidence: 99%
“…Of these selected mediators, we observed that IL‐1 β expression was significantly higher in clots from patients with large artery atherosclerosis than in those with either cardioembolism or undetermined etiology. IL‐1 is a prototypic proinflammatory cytokine that leads to the recruitment of inflammatory cells by inducing the production of cytokines and chemokines and increasing the expression of adhesion molecules on endothelial cells 18. The term IL‐1 refers to two distinct but related proteins, IL‐1 α and IL‐1 β .…”
Section: Discussionmentioning
confidence: 99%